Ablation of idiopathic ventricular tachycardia originating from posterior mitral annulus by using electroanatomical mapping - Aksu, Tolga (Int Med Case Rep J, 2015)
Idiopathic ventricular tachycardia (IVT) is an important type of arrhythmia, which has distinct electrocardiographic features and treatment options. Most of the cases originate from right ventricular outflow tract and less frequently from the left ventricular outflow tract. IVTs originating from mitral annulus are rare, and little is known about the efficacy of radiofrequency catheter ablation in this form. We hereby present a rare case of IVT arising from posterior mitral annulus. The electrocardiographic, electrophysiological, and electroanatomical characteristics of this tachycardia are discussed.